Karl Helfferich und Rudolf Hilferding über Georg Friedrich Knapps "Staatliche Theorie des Geldes": Geldtheorien zur Zeit der Hyperinflation von 1923 - Jan Greitens (IBF - Institut für Bank- und Finanzgeschichte, 2019)
– The monetary ideas of Georg Friedrich Knapp have recently resurfaced in the context of the Modern Monetary Theory whose representatives see themselves in his tradition. The historical debate on Knapp's "State Theory of Money," which divided opinion when it was first published in 1905 as well as during the period of German inflation that peaked in 1923, is therefore of particular interest. Knapp describes money largely from a legal perspective, labelling it a "creature of the legal order". The principle "Mark = Mark" reflects his nominalistic approach. However, he opposed monetary state financing, and favoured balanced governmental budgets. One of his students, Karl Helfferich, was the most influential monetary theorist in the German Reich during the first decades of the 20th century. In defining Knapp's view as an ultimate ideal that might be realised at some point, and his own metallist approach as a practical necessity, he tries to reconcile his teacher's nominalistic theory on the one hand with his own gold currency-principles on the other.The monetary theory of the Marxist Rudolf Hilferding was eclectic, but he moved closer to a nominalistic approach after studying Knapp's theory. During inflation, Helfferich, a representative of the Balance of Payments Theory, and Hilferding, more of the Quantity Theory of Money, also held opposing views in the public debate on the monetary reforms required. The relationship between the three authors was highly complex. While Helfferich and Knapp were personally close, they were far apart in their theories although Helfferich tried to conceal this fact. Hilferding and Helfferich, meanwhile, held similar views on some practical points, such as the necessity of a gold-based currency, but clashed vehemently on a personal level. (The English version of this paper is available at: http://hdl.handle.net/10419/216102)
Keywords: B31; E31; N14; 330